"Prosecutors charge me, police watch after me" -The intertwining of authenticity, crime, and gang life in Finnish 'gangsta rap' music - Aberg, Erica; Westinen, Elina (SAGE PUBLICATIONS LTD, 2025)
This article delves into Finnish 'gangsta rap', from the perspective of authenticity, a key trope in translocal hip hop culture. More specifically, we analyse four Finnish 'gangsta rap' videos and their lyrics by artists who received considerable attention in the Finnish media during 2021-2022. While the media argue that we are facing a new situation of commodified gang violence mediated by 'gangsta rap' - or, to be precise, drill-influenced music, which has been termed as 'gangsta' by the media - our analysis, drawing on previous research in cultural criminology and hip hop studies, suggests that both the music and the criminal activities, as well as the responses to them, are similar to those observed in earlier US and UK research. However, what makes Finland a globally interesting case study in studying gangsta rap and their assumed connection to street gangs is (i) a relatively small number of immigrants and people of colour, (ii) substantial media attention based on official discourse and high trust in the authorities, and (iii) the escalation of gang violence in the neighbouring Sweden and its anticipated trickle-down effect to Finland. We argue that, in exploring the complex interconnections between authenticity, crime and gang life, one needs a 'placed', street literate understanding, the lack of which may arbitrarily stigmatise certain groups of people and certain musical styles.